Extracellular electron transfer-dependent anaerobic oxidation of ammonium by anammox bacteria - Shaw, Dario R.; Ali, Muhammad; Katuri, Krishna P.; Gralnick, Jeffrey A.; Reimann, Joachim; Mesman, Rob; van Niftrik, Laura; Jetten, Mike S. M.; Saikaly, Pascal E. (Nature communications, 2020)
Anaerobic ammonium oxidation (anammox) bacteria contribute significantly to the global nitrogen cycle and play a major role in sustainable wastewater treatment. Anammox bacteria convert ammonium (NH 4 + ) to dinitrogen gas (N 2 ) using intracellular electron acceptors such as nitrite (NO 2 − ) or nitric oxide (NO). However, it is still unknown whether anammox bacteria have extracellular electron transfer (EET) capability with transfer of electrons to insoluble extracellular electron acceptors. Here we show that freshwater and marine anammox bacteria couple the oxidation of NH 4 + with transfer of electrons to insoluble extracellular electron acceptors such as graphene oxide or electrodes in microbial electrolysis cells. 15 N-labeling experiments revealed that NH 4 + was oxidized to N 2 via hydroxylamine (NH 2 OH) as intermediate, and comparative transcriptomics analysis revealed an alternative pathway for NH 4 + oxidation with electrode as electron acceptor. Complete NH 4 + oxidation to N 2 without accumulation of NO 2 − and NO 3 − was achieved in EET-dependent anammox. These findings are promising in the context of implementing EET-dependent anammox process for energy-efficient treatment of nitrogen. Bacteria capable of anaerobic ammonium oxidation (anammox) produce half of the nitrogen gas in the atmosphere, but much of their physiology is still unknown. Here the authors show that anammox bacteria are capable of a novel mechanism of ammonium oxidation using extracellular electron transfer.